Profil pelaksanaan pembelajaran Tematik Terpadu di SDN Gugus 2 kecamatan Kedungkandang Malang - Vina Gayu Buana (Program Studi PGSD STKIP PGRI Banjarmasin, 2019)
this research describes implementation of integrated thematic in grade IV of elementary school. This research is qualitative description. The subject of research were teacher of grade IV in elementary school. The setting of research was SDN Gugus 2 of sub-district Kedungkandang. Instruments of research were guide observation, guide interview, and recorded. Data was analyzed by reduction, presentation, conclusion, and verification of data. The result of data showed that the teacher implemented the integrated thematic with scientific approach. Instructional thematic was implemented by linking multiple subjects of a thema in a instructional process. In instructional process, the teacher implemented scintific approach by five steps. They were observing, asking, collecting information, and communication.